The safety and performance of the Spectra Optia apheresis system platelet depletion protocol in patients with elevated platelet counts. Issue 6 (14th September 2022) - Lopert, Pamela; Abdelrahman, Sohair; Graybill, Christopher A.; Rhodes, Jack; Sørensen, Betina; Li, Ming; Hu, Yu; Wu, Depei; Liu, Ligen; He, Pengcheng; Zhang, Xuejun; Huang, Fen; et al.
Abstract: Background: Thrombocytosis is a presenting and progressive clinical feature found in multiple disease states. It is characterized by high platelet (PLT) counts (>450 × 10 9 /L) and can lead to thrombohemorrhagic events. Thrombocytapheresis or platelet depletion (PLTD) can be performed in acutely symptomatic patients suffering from thrombocytosis and may reduce or prevent acute serious complications associated with thrombocythemia thereby enabling patients to receive potentially curative high‐dose chemotherapy. Methods: This report details the results from 2 clinical studies, one conducted in the European Union (EU) and one in the People's Republic of China, assessing the PLTD procedure on the Spectra Optia Apheresis System. The primary objective of both studies was to assess the safety and performance of the PLTD procedure in patients with elevated PLT counts. Results: Data were collected from 56 participants completing 64 PLTD procedures. The mean percent change in PLT count and collection efficiency (CE1) was 55.1% and 68.5%, respectively. In the EU study, 6 participants experienced a total of 9 adverse events (AEs) and in the China study, 44 participants reported a total of 212 AEs. In both studies, the majority of AEs reported were Grade 2 or lower and no serious AEs, unanticipated adverse device effects, or AEs leading to death were reported. Conclusions: The data collected within these studies indicate that the PLTD procedure is well tolerated and effective at reducing circulating PLTs in patients suffering from thrombocytosis as evaluated by a percent decrease in PLT count, CE1, and AE incidence.